Beyond the walls of the school: Risk factors and children and youth in the Gulf - Maha Al-Hendawi (17337730) (2014)
UNESCO has reported that progress on the Education For All movement has been slow in the Arab world, including the countries of the Gulf Cooperation Council. The low levels of achievement on national and international assessment tests in these states support this judgment. In this conceptual paper, we explore risk factors that can impact the education and educational outcomes of children and youth, reviewing the existing literature and considering its applicability to the Gulf. We argue that risk factors exist in the Gulf that affect short- and long-term outcomes and create barriers to success. Three such factors identified include societal change, familial factors, and gender. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2014.1